Ento(o)mics: the intersection of 'omic' approaches to decipher plant defense against sap-sucking insect pests. (August 2020) - Zogli, Prince; Pingault, Lise; Grover, Sajjan; Louis, Joe
Abstract : Plants are constantly challenged by insect pests that can dramatically decrease yields. Insects with piercing-sucking mouthparts, for example, aphids, whiteflies, and leaf hoppers, seemingly cause less physical damage to tissues, however, they feed on the plant's sap by piercing plant tissue and extracting plant fluids, thereby transmitting several plant-pathogenic viruses as well. As a counter-defense, plants activate an array of dynamic defense machineries against insect pests including the rapid reprogramming of the host cell processes. For a holistic understanding of plant-sap-sucking insect interactions, there is a need to call for techniques with the capacity to concomitantly capture these dynamic changes. Recent progress with various 'omic' technologies possess this capacity. In this review, we will provide a concise summary of application of 'omic' technologies and their utilization in plant and sap-sucking insect interaction studies. Finally, we will provide a perspective on the integration of 'omics' data in uncovering novel plant defense mechanisms against sap-sucking insect pests.